Path coefficient analysis in rubber tree clones - Vasconcellos, Maria Elizabeth da Costa; Abreu, Clóvis Pompilio de (Pesquisa Agropecuaria Brasileira, 2014)
Considering nine characters of clones of a one-year old rubber tree clones the use of the path coefficient was analyzed. In the analysis the estimated values of genetic correlation coefficients of yield by early microttaping test applied for young plants were considered. The characters total number of latex vessel rings, bark tickness and diameter of the latex vessel rings showed a strong influence as much direct as indirect in the yield of rubber in the studied clones. A negative influence as much direct as indirect for the density of latex vessels per 5 mm per ring in the rubber yield was observed.